2019
DOI: 10.1080/00218464.2019.1565756
|View full text |Cite
|
Sign up to set email alerts
|

Strain-based methodology for mixed-mode I+II fracture: A new partitioning method for bi-material adhesively bonded joints

Abstract: The dissemination of composite materials introduces applications of hybrid structures with composite and metal parts. The development of reliable methodologies to evaluate the performance of these structures is required. In this work, the mixed-mode fracture behaviour of a bi-material adhesively bonded joint is investigated. A new strain-based criterion for the design of the Mixed-Mode Bending (MMB) bi-material specimen is suggested. A new analytical partitioning method based on the 'global method' is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In their research, it is concluded that the mixed mode ratio (MMR) is reduced by a factor of 5 when using the proposed criterion in comparison with the flexural stiffness‐based criterion. Then, Arouche et al investigated the mixed mode debonding behavior of a bimaterial adhesively bonded joint. In their research, a new strain‐based criterion for the mixed mode bending (MMB) specimen is used to predict the fracture mode partitioning, analytically.…”
Section: Introductionmentioning
confidence: 99%
“…In their research, it is concluded that the mixed mode ratio (MMR) is reduced by a factor of 5 when using the proposed criterion in comparison with the flexural stiffness‐based criterion. Then, Arouche et al investigated the mixed mode debonding behavior of a bimaterial adhesively bonded joint. In their research, a new strain‐based criterion for the mixed mode bending (MMB) specimen is used to predict the fracture mode partitioning, analytically.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is trivially fulfilled, for instance, by homogeneous laminates with mid-plane delaminations (for which b 1 = b 2 = 0, d 1 = d 2 , and h 1 = h 2 ) or symmetrically-stacked laminates with mid-plane delaminations (for which b 1 = −b 2 , d 1 = d 2 , and h 1 = h 2 ). Besides, the balance condition is satisfied by homogeneous sublaminates with bending stiffness ratio D 1 D 2 = h 1 h 2 [38,58]. More generally, it is possible to conceive of non-trivial stacking sequences, where the upper and lower sublaminates have unequal thicknesses, but fulfil the balance condition [59,60].…”
Section: Solution Strategymentioning
confidence: 99%
“…The strain-based partitioning method (SBM), proposed by Arouche et al, [42] introduced a new criterion for the fracture mode partitioning. The main difference in comparison with the WM lies on the condition for pure mode I: it incorporates the condition of strain equivalence for mode pure mode I, identified by Ouyang [44] and confirmed by Wang et al [41] In the case of pure mode II, similarly to WM, the SBM assumes that it is produced when both arms have the same curvature, as observed by Mollón et al [45] Therefore, the partitioning assumptions become: (i) the longitudinal strain distribution at the faying surfaces of both arms must be identical in order to produce pure mode I; and (ii) pure mode II is obtained when the curvature in the two arms are the same.…”
Section: Strain-based Partitioning Methodsmentioning
confidence: 99%
“…Then, Arouche et at. [42,43] extended this criterion for the mixed-mode fracture characterization of asymmetric cracks and introduced a new method: the strain-based partitioning method (SBM). The SBM is directly derived from beam analysis but uses different partitioning assumptions from the traditional WM.…”
Section: Introductionmentioning
confidence: 99%